Kecemasan dengan kualitas hidup pasien yang menjalani hemodialisis - Edriyani Yonlafado Simanjuntak; Amila Amila; Vivi Anggraini (Health Sciences and Pharmacy Journal, 2020)
Chronic Kidney Failure (CRF) is a condition of chronic kidney function decline that is progressive and irreversible. One of the effective actions in handling this condition is hemodialysis. CRF patients undergoing hemodialysis therapy mostly experience anxiety and decreased quality of life. This study aims to determine the relationship of anxiety with quality of life in CRF patients undergoing hemodialysis at Rasyida Kidney Hospital Medan. The research method used correlation analytic with cross sectional approach. The study population was all patients undergoing hemodialysis with a sampling technique that was purposive sampling with a total sample of 76 people. The research instrument used the Zung Self Rating Anxiety Scale (ZSAS) and WHOQOL-BREF questionnaire. The results of the study were analyzed using the Spearmen Rank test. The results of this study indicated the anxiety of the majority of respondents with a moderate category of 49 respondents (64.5%) and the quality of life of patients undergoing majority hemodialysis with a bad category of 42 respondents (55.3%). Spearmen rank test analysis showed that there was a relationship between anxiety and the quality of life of CRF patients undergoing hemodialysis with value of p = 0.006 p